Clinical features, diagnosis, and treatment outcome of Rhino-orbito-cerebral mucormycosis: A 2-year experience at a tertiary care center - Ashok Vivekanand; Shital Nannaware (Kerala Journal of Ophthalmology, 2023)
Context: The incidence of the fungal disease, mucormycosis, is showing a steady increase among the Indian population in recent past years. Considered as a form of acute invasive fungal rhinosinusitis, the disease is characterized by high morbidity and mortality rates. Aims: The aim of this study was to study the clinical presentations, species distribution, and treatment outcomes in patients of rhinomucormycosis. Settings and Design: This was a tertiary care hospital-based case series. Subjects and Methods: The study was carried out between June 2018 and February 2020. All laboratory-confirmed cases of rhinomucormycosis were included in the study population. Results: Sixteen cases of histopathologically and microbiologically confirmed cases of rhinomucormycosis were included in the study. The study population included ten females and six males. Diabetes mellitus was found to be the most common comorbid condition in the study group (81.25%). Among the study group, swelling of cheek and thick blood-stained discharge were the most common presenting symptoms (9 cases out of 16). The most common clinical type was rhino-orbital mucormycosis. Rhizopus was the most common species encountered (87.5%). In spite of utmost care, treatment outcome was not favorable in most of the cases. Conclusion: An early diagnosis of mucormycosis in the background of immunocompromised status can help in initiating appropriate treatment, thereby reducing the morbidity and mortality associated with this disease condition.